Assessment of an Tentative Novel Body of X-Ray tube in order to Decrease the Applicability Limitation in Medical Practice - Navvabpour, Mojtaba; Navvabpour, Mohammad; Ghane-e Dehkordi, Mohammad; Nazari Moghadam, Hossein; Aazami, Seyed Mohammad Reza (Archives of Advances in Biosciences, 2014)
The output of X-ray, especially in the field of required energy for diagnosing the disease is very low (in diagnosing lamps, it is less than 1%). In this kind of lamps the rest of the electrical energy is transformed to heat. This considerable amount of heat induces a myriad of too many limitations in choosing higher levels of radiation, particularly in specialized techniques. This process is the outcome of X-ray generating mechanism; thus, one of the proper solutions to reduce the limitations caused by generating high heat is enhancing the cooling rate in these lamps. In this project, the design and alloy of the framework, surface and the substance were altered in a manner whereby the cooling rate increases or heat accumulation in lamps decreases. This surface was designed in the shape of a two-part disc with wings whose substance is the same as the framework. The substance of the framework is made of an alloy of copper and chromium. The disc shape of the framework and its aerodynamic compatibility further expose its contacting surface to the air.  This contacting surface can be expanded to 10 times more than the ordinary frameworks. The heat conductivity coefficient of this alloy is approximately 220 w/ mk, which in comparison with the heat conductivity coefficient of the ordinary lamps framework, being about 10, is 22 times more. The results of the tests reveal that the cooling rate of this framework is 10 times (or 1000%) more than the ordinary one. This process reduces the limitations of choosing radiation factors with the same proportion